Seed production technology of sunflower (Helianthus annuus): An update: Seed production technology of sunflower (Helianthus annuus): An update - MAHAK SINGH; AMIT TOMAR; SANJAY KUMAR (Journal of Oilseeds Research, 2023)
Sunflower (Helianthus annuus) belonging to the family Asteraceae was introduced in India in 1969 and became one of the important oilseed crops. The oil is used for culinary purpose, preparation of cosmetics etc. Seed production can be taken up in all the three seasons like kharif, rabi and summer. For rainfed conditions June – July and October – November and for irrigated conditions April – May and December – January is suitable for seed production. Sunflower oil is light yellow in colour and possesses good odour, which can be used for a variety of cooking purposes like any other edible oil. Sunflower oil is a rich source of linoleic acid (64%), which helps in washing out of cholesterol deposition in the coronary arteries of theheart, and thus it is good for heart patients. The oil is used for manufacturing hydrogenated oil.Its oil is also used in manufacture of soaps and cosmetics. The sunflower cake contains 40-44% high quality protein. It is ideally suited for poultry and livestock rations. The sunflower kernels can be eaten raw or roasted. It can also be used for manufacturing baby foods.